2010
DOI: 10.1111/j.1365-2966.2010.16462.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotational asymmetry of pulsar profiles

Abstract: We analyse the influence of rotation on shapes of pulse profiles of fast-rotating (millisecond) pulsars. Corotation has two opposing effects: 1) the caustic enhancement of the trailing side (TS) by aberration and retardation (AR), which squeezes the emission into a narrower phase interval; 2) the weakening of the TS caused by the asymmetry of curvature radiation about the dipole axis. Analysis of the radii of curvature of electron trajectories in the inertial observer's frame (IOF) enables these two effects to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 27 publications
3
32
0
Order By: Relevance
“…The MP shows an interesting evolution between 1400 MHz and 600 MHz. Observations with the Green Bank Telescope at 1400 and 800 MHz (not shown here) have revealed that at those frequencies this pulsar's MP may be composed of up to six components (Dyks et al 2010). At 150 MHz, two components of the MP are clearly visible, of roughly equal magnitude and much more clearly separated than at higher frequencies.…”
Section: Psr J1012+5307mentioning
confidence: 99%
“…The MP shows an interesting evolution between 1400 MHz and 600 MHz. Observations with the Green Bank Telescope at 1400 and 800 MHz (not shown here) have revealed that at those frequencies this pulsar's MP may be composed of up to six components (Dyks et al 2010). At 150 MHz, two components of the MP are clearly visible, of roughly equal magnitude and much more clearly separated than at higher frequencies.…”
Section: Psr J1012+5307mentioning
confidence: 99%
“…This has several consequences: 1) As shown with the horizontal arrows, the central component ('core') lags the centroids of pairs of outer components. 2) The leading components become wider than the trailing ones (see Ahmadi andGangadhara 2002, andDyks et al 2010b for observational evidence). 3) Because δcut is smaller on the LS, for decreasing ν the leading components departure from the 'core' faster than the trailing components.…”
mentioning
confidence: 99%
“…Thus the extension of the LS emission over a long stretch of pulse longitude occurs also in the stream model, along with the simultaneous pile up of emission on the TS (see. Dyks et al 2010b). 5) Since the consecutive ellipses in the trailingmost stream are more overlapping with each other, the spectrum is more broadband on the TS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rotation also influences the intensities of the leading and trailing components of the profile (Blaskiewicz et al 1991;Thomas & Gangadhara 2007). Dyks et al (2010) analyzed the rotation and found two competing effects: the enhancement of the trailing side caused by aberration and retardation (AR) and the weakening of the trailing side caused by the rotation-induced asymmetry of curvature radius. In the pioneer paper, Blaskiewicz et al (1991) calculated only the emission of particles with velocity pointing towards the observer, and did not consider the emissions from particles of nearby field lines, which may still beam towards us.…”
Section: Introductionmentioning
confidence: 99%